Prevalence of Aflatoxin Contamination in Herbs and Spices in Different Regions of Iran - Payam KHAZAELI; Mitra MEHRABANI; Mahmoud Reza HEIDARI; Gholamreza ASADIKARAM; Moslem LARI NAJAFI (Tehran University of Medical Sciences, 2017)
Background: Mycotoxins are natural toxins, produced by several fungal species and are associated with morbidity or even mortality in animals, plants, and humans. In this study, 120 samples of herbs and spices in both bulk and packaged forms were prepared in order to measure aflatoxin level in different regions of Iran Methods: The aflatoxin was extracted during Mar to May 2015, using 80% methanol and then purified via immunoaffinity column. Measurements were performed, using high-performance liquid chromatography, equipped with a fluorescence detection system at excitation and emission wavelengths of 365 and 435 nm, respectively. Results: The highest prevalence of aflatoxin contamination in food products was attributed to aflatoxin B1 (30.8%). In addition, the highest prevalence of aflatoxin contamination was reported in red pepper (100%). Examination of effective factors indicated the substantial impact of moisture on aflatoxin level (P=0.046). Conclusion: Even at low levels of aflatoxin, contamination could be a serious threat, given the prevalent use of spices (either raw or not) as ingredients in food preparation. Therefore, regular monitoring of spices, especially chili pepper, is highly recommended.